Role of Regulatory Immune Cells and Molecules in Autoimmune Bullous Dermatoses - Cao, Tianyu; Shao, Shuai; Fang, Hui; Li, Bing; Wang, Gang (Frontiers in Immunology, 2019)
Autoimmune bullous dermatoses (AIBD) include a series of typical organ-specific autoimmune diseases characterized by extensive mucocutaneous blisters. It is generally accepted to be caused by pathological autoantibodies that directly target specific adhesion components of the skin or the adjacent mucous membranes. Both innate and adaptive immune systems are critically involved in the misguided immune response against self-antigens. Recent studies have indicated that the dysfunction of regulatory T cells, regulatory B cells, and complement regulatory proteins that play essential roles in maintaining a healthy immune environment is also closely related to immune disorders in AIBD. It is important to summarize these studies, elucidate the changes in these regulatory immune cells and molecules for the pathogenesis of AIBD, and reveal the mechanisms by which they lose their ability to regulate immune disorders. In this review, we highlight the role of regulatory immune cells and molecules in the pathogenesis of pemphigus vulgaris and bullous pemphigoid, the two most representative forms of AIBD, and indicate issues that should be addressed in future investigations.